Abdominal aortic aneurysms, or a relatively large diameter of non-aneurysmal aortas, increase total and cardiovascular mortality: the Tromsø study. - Forsdahl, Signe Helene; Solberg, Steinar; Singh, Kulbir; Jacobsen, Bjarne Koster (International Journal of Epidemiology, 2010)
Background: In a population-based study in Tromsø, Norway, the authors assessed whether an abdominal aortic aneurysm (AAA) or the maximal infrarenal aortic diameter in a non-aneurismal aorta influence total and cardiovascular disease (CVD) mortality. Methods: A total of 6640 men and women, aged 25–84 years, were included in a 10-year mortality follow-up: 345 subjects with a diagnosed AAA and 6295 subjects with a non-aneurismal aorta. Non-aneurismal aortic diameter and prevalent AAAs were categorized into seven groups. Results: In subjects without an AAA, an aortic diameter 30 mm increased age- and sex-adjusted total mortality [mortality rate ratio (MRR) = 3.73, 95% confidence interval (CI) 1.77–7.89] and CVD mortality (MRR = 9.24, 95% CI 4.07–20.97) compared with subjects with aortic diameter of 21–23 mm. An AAA at screening was strongly associated with deaths from aortic aneurysm and was associated with total (MRR = 1.60, 95% CI 1.31–1.96) and CVD mortality (MRR = 2.41, 95% CI 1.81–3.21). This was not explained by deaths due to an AAA. Adjustments for CVD risk factors could fully explain the increased total, but not CVD mortality in subjects with an AAA. Conclusions: An AAA increases total and CVD mortality. In the large majority of subjects with a non-aneurysmal aorta, the diameter does not influence total or CVD mortality. However, in individuals with a maximal diameter >26 mm (2% of the population), a positive relationship is found